Analisis Penerapan Sistem Manajemen Keselamatan Kerja Di Proyek Gedung - Yuliana, Ni Putu Indah; Dewi, I Gusti Ayu Wulan Krisna; Putra, I Gusti Putu Adi Suartika; Yuni, Ni Kadek Sri Ebtha; Wahyudi, I Gede Bambang (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2025)
The increasing development of construction projects has led to an increase of work accidents and insurance claims. This must be followed up with the implementation of a construction safety management system. This action is expected to reduce the number of accidents and illnesses due to work. The purpose of the study is to analyze the value level of implementation of construction safety management system and the factor that causing the discrepancy between the requirements and the implementation. This study uses a qualitative research method with a descriptive format. The results showed that the implementation rate of the Construction Safety Management System was 88.37% with the category of "Satisfactory Implementation". The factor that causing the discrepancy are the contractor leader rarely goes to the field to provide briefings related to occupational safety and health because it has been carried out by the project occupational safety and health management team, the implementation of the construction safety management system is good but there are still some differences because the project being worked on is a building construction project, the composition of the Occupational Safety and Health Management Team in the project is adjusted to the needs of the project so that emergency response officers and first aid officers in accidents are not provided in the field.